The Role of Environmental Management Accounting in Mediating Green Innovation to Firm Value: Moderated by Quality Management - Hidayat, Imam; Hamdani, Hamdani; Abbas, Dirvi Surya; Lam, Nguyen Thanh; Sari, Petty Aprilia (International Journal of Energy Economics and Policy, 2024)
Firm value is an important indicator for increasing the competitiveness of a company amidst very tight business competition. This research aims to obtain empirical evidence regarding the influence of Green Innovation on Firm Value which is mediated Environmental Management Accounting and moderated by Quality Management. The companies that are the object of this research are manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The sampling technique in this research used a purposive sampling method and obtained 65 companies. The multicollinearity test and heteroscedasticity test are used as classical assumption tests. Eviews 12 software with panel data regression analysis was used to test the hypothesis. Based on the research results, it was found that green innovation, environmental management accounting, green innovation have an influence on Firm Value, environmental management accounting has an influence in mediating the relationship between green innovation and Firm Value and quality management can moderate the relationship between green innovation and Firm Value.